Penerapan Model Pembelajaran Problem Based Learning (Pbl) Pada Materi Asam Basa Siswa Kelas Xi Ipa Di Sma Negeri 1 Tenga - Oktaviani Rampi; Emma Pongoh; Joice Caroles (Chemistry Department, Universitas Negeri Manado, 2021)
This research aims to determine the application of problem based learning (PBL) learning models on acid-base material for class XI science at SMA Negeri 1 Tenga. This research was conducted in class XI SMA Negeri 1 Tenga with a sample of 25 people. The research design used was the post-test-only control group design experimental method. The experimental class uses a problem based learning (PBL) model and the control class uses conventional learning. Analysis of hypothesis testing using t-test with a significant level of = 0.05 and success (dk) = 48. The test results obtained show that the results of tcount > ttable or 3.62 > 2.010, thus H0 is rejected and Ha is accepted, and the average the average student learning outcomes of the experimental class were 81.92, which was greater than the learning outcomes of the control class was 72.96. This shows that there is a significant difference between the average score (post-test) of the experimental group and the control group. So it can be concluded that there is a difference in the average learning outcomes of students who use the problem based learning (PBL) learning model with the learning outcomes of students who use conventional learning on acid-base materials.